The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4236/ojapps.2012.23024
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Prey Selection and Growth of Juvenile Pikeperch (<i>Sander lucioperca</i>) over Half a Century in a Changing Lake Võrtsjärv

Abstract: Analysis of historical and recent data is essential to understand how eutrophication and/or climate change might trigger shifts in the feeding mode of fish and trophic dynamics of shallow lakes. To assess long-term changes in the diet and growth of juvenile pikeperch (Sander lucioperca), the prey selection and growth of pikeperch fry from Lake Võrtsjärv was investigated in 2007-2010 and compared with data from 1920 to 1970. Over the observed period, larger cladocerans have become less frequent in the diet as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This has led to larger number small individuals and thereby overdensity of juvenile fish might occur. Additionally, because juvenile fish are able to survive warmer winters despite postponements of the diet shift (Ginter et al, 2011(Ginter et al, , 2012b, the proportions of young individuals in the pikeperch populations have expanded even more. Favourable years for pikeperch growth were identified in both investigated lakes, and based on these observations, we suggest that similar climate effects might have occurred in other lakes within the Peipsi region.…”
Section: Discussionmentioning
confidence: 98%
“…This has led to larger number small individuals and thereby overdensity of juvenile fish might occur. Additionally, because juvenile fish are able to survive warmer winters despite postponements of the diet shift (Ginter et al, 2011(Ginter et al, , 2012b, the proportions of young individuals in the pikeperch populations have expanded even more. Favourable years for pikeperch growth were identified in both investigated lakes, and based on these observations, we suggest that similar climate effects might have occurred in other lakes within the Peipsi region.…”
Section: Discussionmentioning
confidence: 98%
“…fluviatilis fry at 15 mm L S (stage E) indicated the early piscivorous behaviour of this species. Sander lucioperca fry diet in the study area was similar to that observed in other eutrophic lakes (Popova & Sytina, ; Sutela & Hyvärinen, ; Ginter et al ., 2012 a, b ). In this study, S .…”
Section: Discussionmentioning
confidence: 99%
“…The differences in diet composition among the research blocks resulted from a combination of factors, including habitat type, prey abundance, and water depth. Fish feeding differs markedly according to spatial factors, such as habitat type (Platell et al, 2007;Lek et al, 2011), differences in food resources (Mittelbach et al, 1992;Francis and Schindler, 2009), temporal factors, such as seasonal and annual changes in prey species (Hovde et al, 2002;Ginter et al, 2012), and ontogenetic changes (Werner and Gilliam, 1984;Park et al, 2021). Toothfish are top predators that feed on fish and cephalopods.…”
Section: Discussionmentioning
confidence: 99%